Rethinking Intention in STEM Education: Cross-Cultural Insights from the Theory of Planned Behavior - Henie Poerwandar Asmaningrum; Renuka V Sathasivam; Edy Hafizan Mohd Shahali (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This systematic literature review aims to synthesize current knowledge about attitude-intention relationships in STEM education through the Theory of Planned Behavior framework and identify key factors that moderate these relationships across diverse cultural and educational contexts. Methodology: Systematic literature review following PRISMA 2020 guidelines using Scopus database. Comprehensive search strategy with Boolean operators covering Theory of Planned Behavior, attitudes, intentions, and STEM education contexts from 2015-2025. Data extraction using standardized forms, quality assessment with Mixed Methods Appraisal Tool (MMAT), and narrative synthesis with bibliometric analysis using VOSviewer software for thematic clustering and temporal trend analysis. Main Findings: Twenty-six studies from 15 countries revealed robust TPB applicability in STEM contexts with significant cross-cultural variations. Collectivistic cultures demonstrated stronger subjective norms effects (β = 0.28-0.48) while individualistic cultures showed stronger attitude effects (β = 0.41-0.58). Cultural intelligence emerged in 38.5% of studies as critical moderator. Extended TPB models incorporating self-efficacy, environmental support, and readiness factors provided enhanced explanatory power beyond core components. Novelty/Originality of this study: First comprehensive systematic review examining TPB in STEM education with explicit cross-cultural analysis and cultural intelligence integration. Advances existing knowledge by identifying systematic cultural variations in TPB component strength and providing evidence-based framework for culturally responsive STEM education interventions targeting diverse global populations.